Functional evaluation of temporary focal cerebral ischemia: experimental model - Sinésio Grace Duarte; Antônio Dorival Campos; Benedicto Oscar Colli (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Despite cerebral ischemia being a frequent clinical pathologic state, the tolerance of neural tissue to oxygen absence and to reperfusion is controversial. This study aims to evaluate the effects of focal cerebral ischemia/reperfusion, by analyzing the mitochondrial respiration. METHOD: Sixty-four adult rats underwent focal cerebral ischemia by middle cerebral artery occlusion, during 15, 30 and 60 minutes, followed by 10 minutes or 19 hours of reperfusion. The effects of ischemia were analyzed measuring the O2 consumption by mitochondria in the ischemic and non-ischemic areas. RESULTS: There was compromise of the mitochondrial respiration after 30 and 60 minutes of ischemia, followed by 10 minutes of reperfusion but there was no alteration in this function after 19 hours of reperfusion. CONCLUSION: Compromise of the mitochondrial function occurred after 30 minutes of ischemia but, until one hour of ischemia, if the reperfusion was prolonged there was no evidence of ischemic/reperfusion injuries.